Aerosol science for industrial hygienists - Vincent, James H. (Pergamon : Elsevier Science, 1995)
Aerosols in workplace atmospheres have been - and continue to be - a major focus of industrial hygiene. Although there are many existing texts on aerosol science and on occupational health respectively, this new book sets out to be complementary to these and to provide a link between the two fields. In particular, the central concept of worker exposure leads to a structured approach which draws together wide-ranging aspects of aerosol science within the occupational health framework. Introductory chapters are concerned with the nature and properties of aerosols, and how they are generated in the occupational environment. The book then goes on to provide a description of the fundamental mechanical properties of aerosols, in particular those mechanical properties associated with the motion of airborne particles (which govern particle transport, inhalation, deposition, sampling and control). There follows a description of the optical properties of workplace aerosols since these are important in the visual appearance of aerosols and in many aspects of measurement. The central core of the book deals with the processes which govern the nature of exposure to and the subsequent fate and effects of airborne particles, leading to a rational framework for standards, measurement and control. Finally, a chapter is added which relates what has been said about aerosols to gaseous and vapour contaminants. The book is aimed at graduate students and practitioners in industrial hygiene and other occupational (and environmental) health disciplines.
Keywords: Aerosols -- Toxicology.; Indoor air pollution.; Industrial hygiene.; elektronické knihy; electronic books